Ethnic-Racial Studies in Geography: The Case of Afro-Brazilian Culture and Its Spatialities: The Case of Afro-Brazilian Culture and Its Spatialities. (Interdisciplinary Studies Journal, 2021)
This work is the result of a pedagogical experience related to guided teaching, with the theme of Geography and Afro-Brazilian culture. The objective was to contribute to the deconstruction of prejudice and discriminatory attitudes through pedagogical practice that encourages a critical view of Brazil's cultural pluralities. Based on this, the aim was to include the study of African influence in the formation of Brazilian society, promoting debates that build knowledge about the historicity of African identities transferred through generations, while also historicizing the contribution of the spatial organization of Black people, emphasizing current spatialities at different moments of space-time. Methodologically, the teaching practice was carried out in stages: 1) problematization of the theme in the curriculum content and pedagogical plan of schools; 2) expository lecture with the presentation of authors who work with Afro-Brazilian culture; 3) seminars with student groups. The teaching practice was conducted with future educators in the Geography course at the Federal University of Santa Maria, within the compulsory course on Cultural Geography. The theme contributed to the students' broader understanding of ethnic-racial issues, with an emphasis on Afro-Brazilian culture, which demands extensive educational debate and applicability in schools.
Keywords: Geography; Cultural Pluralities; School